Enhancing the society's social capital accumulation - Doris Padmini Selvaratnam,; Madeline Berma,; Nor Aini Haji Idris,; Norlaila Abu Bakar,; Poo Bee Tin, (Penerbit Universiti Kebangsaan Malaysia, 2008)
There are various social ills plaguing the society today (i.e. juvenile,delinquency, crimes, murder; gangsterism, abandonment of the elderly, domestic violence, etc.). This can be attributed to various factors ranging fiom peer pressure, mental problems, poverty and marginalisation and eroding moral values. In a society that has experienced a rapid economic growth and a steady increase in the income per capita, it is thus an alarming factor if there is an increase in social problems and an increase in government expenditure to curb this problem. Social capital through effective networking is seen as an avenue to enhance positive social values and contribute towards a harmonious society. This research investigates the social problems in socieiy, the total expenditure incurred by the government to eradicate these problems, the wealth of the society and to finally identifv the new types of social capital in society.